Do fecal odors from native and non‐native predators cause a habitat shift among macropods?. (26th December 2014) - Cox, Tarnya E.; Murray, Peter J.; Bengsen, Andrew J.; Hall, Graham P.; Li, Xiuhua
ABSTRACT: Predator‐odor‐based repellents have benefits as humane, non‐lethal management tools that may reduce the need for lethal control in some areas. Macropods (such as kangaroos and wallabies) are iconic Australian native marsupials; however, some are considered important rangeland pests, and their presence in the urban and peri‐urban environment often results in conflict. The management of these macropods is a contentious and volatile issue. We evaluated lion ( Panthera leo ), Sumatran tiger ( P. tigris sumatrae ), and dingo ( Canis lupus dingo ) fecal odors as short‐term odor‐based repellents for wild eastern grey kangaroos ( Macropus giganteus ) and red‐necked wallabies ( M. rufogriseus ). These odors were used to 'protect' highly palatable food sources; with any food not consumed (residue) collected and weighed each day. Trials were conducted at Long Grass Nature Reserve in Queensland, Australia from 9–29 January 2009. Both eastern grey kangaroos and red‐necked wallabies relocated a minimum of 100 m away from the food station treated with lion odors on the first day of the trial. As a result of this spatial shift, more food was consumed at the control food stations than at any food station treated with predator odors (regardless of predator). In particular, eastern grey kangaroos never fed from a single predator‐odor food station. An increase in vigilance behaviors was observed for both macropod species, and red‐necked wallabies were more likely to exhibit vigilance behaviors than feeding behaviors at predator odor food stations. There was no difference in food residue between any predator odors and these food stations were only visited on the first day of the study. Use of predator fecal odors may repel macropods from highly palatable food sources, and predator fecal odors also may be useful for macropod relocation. © 2014 The Wildlife Society.